SVC sizing optimization using Ant Colony Optimization (ACO) technique / Mohd Nur Izuan Hamdan - Hamdan, Mohd Nur Izuan (2010)
This project presents the application of Ant Colony Optimization (ACO) technique for the determination of optimal sizing of Static Var Compensator (SVC) installed on a transmission line for loss minimization and voltage profile stability in power system IEEE reliability test system was used for validation purposes. SVC is the one of the Flexible AC Transmission System (FACTS) devices. In recent practice, the use of FACTS devices has been proposed for enhancement of power grid protection and control in power system by improving the stability, reduction of losses and generation cost and improves the loadability of the system. However, prohibitive cost is major stumbling block for utility company to install more than a few FACTS devices on any power grid. Therefore, with this project, the optimal sizing of SVC for solving the loss and voltage stability problems will be determined.